KOMPOSISI DAN STRUKTUR KOMUNITAS ZOOPLANKTON PADA KEDALAMAN YANG BERBEDA DI SEKITAR KERAMBA NAGARI KOTO GASANG DANAU MANINJAU KABUPATEN AGAM - Sari, Ravita Gusmala; Ardi, Ardi; Abizar, Abizar (Pendidikan Biologi, 2013)
ABSTRACTLake Maninjau has a location in Kecamatan Tanjung Raya, Kabupaten Agam, West Sumatera. Lake Maninjau has a function as a society jobs like make a fish pond. There are fish pond got the influent toward the composition of organisme in the lake, one of them is zooplankton. The purpose of this research was to know the composition and structure of zooplankton community with physica chemical water factor in different under in arround the fish pond of lake Maninjau. This research was done in March until May 2013. The location of the research was done by using stratified random sampling method with determined one research station. In the station determined three took sample method were in surface with the deep 4m and deep 8m. The samples by using water pomp machine and planktonet. They identified at took Laboratorium of STKIP PGRI west Sumatera. Temperature, pH and DO measured in the field and Nitrogen totaily done in water environmen laboratorium UNAND Padang. The result of research are got 4 classes zooplankton, phytomastigophorea with one genous (Peridinium), Monogononta 7 genous (Branchionus, Colurella, Filinia, Keratella, Lepadella, Lycane, and Tricocerca), Digononta was 1 genous (Macrotrachela) and Crustacea got 4 genous (Cylops, Macrothrix, Pleuroxus and Nauplius). The highest diversity indexs got level III in deep 8m, 2,43 and the lowert got level I, 1.95 while in level II was 2,29. Measure of water quality in lake Maninjau Kabupaten Agam was temperature 2,9-30ÂºC, pH 8,9-9, Desolved Oxygen (DO) 6,8-8,8 mg/l and the total of nitrogen 1,75-3,25 mg/l.